2021
DOI: 10.1523/jneurosci.2592-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

G-Protein-Coupled Estrogen Receptor (GPER) in the Rostral Ventromedial Medulla Is Essential for Mobilizing Descending Inhibition of Itch

Abstract: Chronic itch is a troublesome condition and often difficult to cure. Emerging evidence suggests that the periaqueductal gray-rostral ventromedial medulla (PAG-RVM) pathway may play an important role in regulation of itch, but the cellular organization and molecular mechanisms remain incompletely understood. Here, we report that a group of RVM neurons distinctively express the G protein-coupled estrogen receptor (GPER), which mediates descending inhibition of itch. We found that GPER + neurons in RVM were activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 59 publications
3
16
0
Order By: Relevance
“…We obtained a line of Gper gene knockout rats (28,30), which showed significant reduction of GPER immunofluorescence in the RVM (Supplemental Figure 7). We compared the level of RVM neuronal activity between wild type and Gper -/rats in chronic inflammatory pain conditions by c-Fos immunostaining conducted at day 7 following intraplantar injection of CFA (with saline as control).…”
Section: Gper Drives Descending Facilitation Of Pain and Morphine Tol...mentioning
confidence: 99%
See 1 more Smart Citation
“…We obtained a line of Gper gene knockout rats (28,30), which showed significant reduction of GPER immunofluorescence in the RVM (Supplemental Figure 7). We compared the level of RVM neuronal activity between wild type and Gper -/rats in chronic inflammatory pain conditions by c-Fos immunostaining conducted at day 7 following intraplantar injection of CFA (with saline as control).…”
Section: Gper Drives Descending Facilitation Of Pain and Morphine Tol...mentioning
confidence: 99%
“…Wild type and transgenic Sprague-Dawley rats (male and female, either adult, 220-250 g, 10-12 weeks old, or neonatal, P12-15 days) and C57/BL6 mice were housed (4 animals per cage) in a temperature (22-25 °C) and humidity (50%) controlled room with a 12/12 h light/dark cycle, with food and water being available ad libitum. Gper-deficient (Gper -/-) rats (28) and mice (30) were generated by the Bioray Biotechnology company in Shanghai.…”
Section: Animalsmentioning
confidence: 99%
“…It was recently reported that activation of neurons in RVM that express the G-protein-coupled estrogen receptor (GPER) suppresses signs of acute and chronic itch ( Gao et al, 2021 ). It is currently not known if GPER-expressing neurons co-express Tacr1.…”
Section: Discussionmentioning
confidence: 99%
“…Descending modulation is also thought to underlie stress mediated changes in pain threshold, with acute stress inhibiting and chronic stress facilitating nociceptive transmission ( Butler and Finn, 2009 ; Fields, 2000 ; Jennings et al, 2014 ; Wager and Atlas, 2015 ). Recent studies indicate that the spinal transmission of pruriceptive information is also under descending modulatory influences, but it is not known whether itch is modulated in the same way as pain ( Agostinelli and Bassuk, 2021 ; Gao et al, 2021 ; Gao et al, 2019 ; Koga et al, 2020 ; Liu et al, 2019 ; Samineni et al, 2019 ; Wu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Descending modulation is also thought to underlie stress mediated changes in pain threshold, with acute stress inhibiting and chronic stress facilitating nociceptive transmission (Butler & Finn, 2009;Fields, 2000;Jennings et al, 2014;Wager & Atlas, 2015). Recent studies indicate that the spinal transmission of pruriceptive information is also under descending modulatory influences, but it is not known whether itch is modulated in the same way as pain (Agostinelli & Bassuk, 2021;Gao et al, 2021;Gao et al, 2019;Koga et al, 2020;Liu et al, 2019;Samineni et al, 2019;Wu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%